Perturbed convective wave equation for low-to-medium Mach number subsonic flows - Schoder, S.; Mohamadi Bagheri, Eman; Bogey, C.; Bailly, C. (Journal of Sound and Vibration, 2026)
A generalization of the perturbed convective wave equation is proposed. It allows extracting the acoustic field and the vortical dynamics from a compressible high-fidelity flow simulation. The wave equation computes the acoustic velocity potential, with a source term based on a source potential. This source potential describes the pressure dynamics of vortices and is identical to the incompressible pressure for incompressible-modeled flows. The application to an isothermal, subsonic two-dimensional mixing layer sound generation problem validates the wave equation. The results of the acoustic far-field pressure are comparable to the direct numerical reference solution, deviating less than 1.8dB.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Aeroacoustics; Compressible flow; Shear layer; Vortex interactions